Developments and convergence of real housing prices in Poland during the COVID-19 pandemic: focus on voivodeship capitals - Weremczuk, Arkadiusz; Wielechowski, Michał; Wrzesińska-Kowal, Joanna (Turystyka i Rozwój Regionalny, 2021)
The paper aims to present and assess the changes in real housing prices in Poland during the COVID-19 pandemic. We analyse transaction prices of residential premises in a multi-family housing (apartments) in the primary and secondary markets within 16 administrative capitals of voivodeships. We use quarterly data on House Prices Database collected by the National Bank of Poland and data on quarterly price indices of consumer goods and services from Statistics Poland. The research period covers the period 2018-2021, with distinction into COVID-19 - and pre-COVID-19 periods. We observe the highest housing prices in Warszawa, Gdańsk, Kraków, and Wrocław, while the lowest in Zielona Góra and Kielce. Surprisingly, the growth rate in real housing prices in the pandemic sub-period is lower than in corresponding pre-COVID-19 period. In the COVID-19 sub-period, we observe the most significant increases in real estate prices in Zielona Góra and Szczecin in the primary market, and Kraków, Lublin, and Łódź in the secondary market. Additionally, we reveal the existence of regional price convergence in the housing market in analysed cities, both in primary and secondary markets. However, we do not observe a common price convergence, but only convergence clubs (city-groups) where the housing prices tend to converge in the COVID-19 sub-period.